Impact of HALO structure on threshold voltage and leakage current in 45nm NMOS device - Salehuddin F.; Ahmad I.; Hamid F.A.; Zaharim A. (2023)
In this paper, we investigate the impact of process parameter like halo structure on threshold voltage (VTH) and leakage current (I Leak) in 45nm NMOS device. The settings of process parameters were determined by using Taguchi experimental design method. Besides halo implant, the other process parameters which used were Source/Drain (S/D) implant and oxide growth temperature. This work was done using TCAD simulator, consisting of a process simulator, ATHENA and device simulator, ATLAS. These two simulators were combined with Taguchi method to aid in design and optimize the process parameters. In this research, the most effective process parameters with respect to threshold voltage and leakage current are oxide growth temperature (71%) and S/D implant dose (47%) respectively. Whereas the second ranking factor affecting VTH and ILeak are halo implant tilt (15%) and halo implant dose (35%) respectively. As conclusions, S/D implant dose and oxide growth temperature have the strongest effect on the response characteristics. The results show that the VTH for NMOS device equal to 0.150V at tox= 1.1nm. The results show that ILeak after optimizations approaches is 51.8?A/m. 2010 IEEE.